2012
DOI: 10.1002/cncr.27441
|View full text |Cite
|
Sign up to set email alerts
|

O6‐methylguanine‐DNA methyltransferase (MGMT) promoter methylation and low MGMT‐encoded protein expression as prognostic markers in glioblastoma patients treated with biodegradable carmustine wafer implants after initial surgery followed by radiotherapy with concomitant and adjuvant temozolomide

Abstract: BACKGROUND: O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation status was proposed as a prognostic biomarker for patients with glioblastoma. However, the prognostic impact of MGMT in patients with newly diagnosed glioblastoma who receive carmustine-releasing wafers (Gliadel) along with temozolomide (TMZ) is still unknown. METHODS: MGMT promoter methylation status and protein expression were analyzed in formalin-fixed, paraffin-embedded tumor specimens obtained from 111 French patients with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 21 publications
1
49
0
1
Order By: Relevance
“…A pharmacokinetic analysis indicated that exposure of the tissue area to carmustine under a concentration-time curve achieved by polymeric delivery was 4-1,200-fold higher compared with that produced by intravenous administration of a higher dose; however, the MGMT status should be considered as the main factor that limits the efficacy of carmustine wafers (12). Indeed, in patients with newly diagnosed GB who underwent surgical resection and received carmustine wafer implants followed by adjuvant radiotherapy and concomitant oral TMZ chemotherapy, MGMT promoter methylation status and low MGMT expression were identified as positive prognostic factors (10). In the present case, the tumor was highly responsive to carmustine wafers, and also exhibited genetic characteristics conferring sensitivity to alkylating agents.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A pharmacokinetic analysis indicated that exposure of the tissue area to carmustine under a concentration-time curve achieved by polymeric delivery was 4-1,200-fold higher compared with that produced by intravenous administration of a higher dose; however, the MGMT status should be considered as the main factor that limits the efficacy of carmustine wafers (12). Indeed, in patients with newly diagnosed GB who underwent surgical resection and received carmustine wafer implants followed by adjuvant radiotherapy and concomitant oral TMZ chemotherapy, MGMT promoter methylation status and low MGMT expression were identified as positive prognostic factors (10). In the present case, the tumor was highly responsive to carmustine wafers, and also exhibited genetic characteristics conferring sensitivity to alkylating agents.…”
Section: Discussionmentioning
confidence: 55%
“…Consequently, carmustine wafers may be implanted concomitantly with these combined standard treatments. The rationale underlying this type of local therapy is to fill the gap between surgery and adjuvant treatments to maintain alkylating treatment pressure on residual tumor cells (10). However, in the present case, carmustine wafers were so effective that the residual tumor had markedly regressed when systemic TMZ chemotherapy was initiated, indicating that the outcome of adjuvant therapy was mainly affected by the carmustine wafers.…”
Section: Discussionmentioning
confidence: 61%
“…Release kinetics were controlled by the diameter of device orifices, the number of orifices, and the solubility of the drug. The inner volume of the reservoir measured 1.5 mL, which allowed for higher drug loading per device volume compared with previous drug delivery devices (10,32). One important innovation in this work was the use of the injection molding process for high-precision device production, which gave reliable and consistent results, including very small tolerances in volume.…”
mentioning
confidence: 95%
“…Localized drug delivery devices provide high drug concentrations to the tumor site while preventing drug degradation and clearance until its release (7,8). The efficacy of current intracranial drug delivery, such as Carmustine wafers, has promise, with a doubling of median survival from 9 to 20 mo in the case of Carmustine wafers (6,9,10). Phase III trial data indicated a 2-to 3-mo survival advantage in Carmustine wafers-treated patients (11), and Carmustine wafers continue to have a role combined with radiation and oral temozolomide (TMZ).…”
mentioning
confidence: 99%
“…With regard to this multimodal treatment, the interesting data recently published in Cancer [9] about the prognostic impact of MGMT in patients with newly diagnosed glioblastoma who receive carmustine-releasing wafers (Gliadel) along with temozolomide must be emphasized. Patients with tumors that harbored MGMT methylation had a significantly longer OS compared with patients who had wild-type MGMT (21.7 months vs. 15.1 months; P00.025).…”
mentioning
confidence: 99%